Penerapan Sanksi Adat “Lais Palolit” dalam Penyelesaian Kasus Pencurian di Desa Boti Kecamatan Kie Kabupaten Timor Tengah Selatan - Shophia Mendora Janische Talan; Simplexius Asa; A Resopijani (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The purpose of this research is to analyze the application of the customary sanction "Lais Palolit" in the settlement of theft cases in Boti Village, Kie Subdistrict, South Central Timor District. The type of research used is empirical research. Empirical research can be interpreted as an approach that looks at a legal reality that exists in society. Based on this type of research, the data sources in this study are primary data and secondary data. The data collection techniques used are interviews, observation and documentation. The data collected will be processed through editing, coding and tabulation stages and data analysis is carried out descriptively, qualitatively and completely. Based on this research, several conclusions can be made, namely that all theft cases that occur within the scope of Boti Village must be resolved through the customary law that applies there by carrying out the customary sanction "Lais Palolit". The form of this customary sanction is the provision of additional property to the perpetrator based on what he took. This customary sanction is considered effective in resolving theft cases in Boti village. This customary sanction is different from the provisions stipulated in article 362 of the Criminal Code, but in its application so far the settlement of all theft cases in Boti village has always used the provisions of customary law and has not used the provisions of national law.